Formation of Persisters in Clinical Isolates of K.pneumoniae Induced with Meropenem, Amikacin, and Their Combination - N. N. Markelova; A. V. Tutelyan; N. G. Sedykh (Антибиотики и Химиотерапия)
A study of induced antibiotic tolerance of clinical isolates Klebsiella pneumoniae sensitive to meropenem and amikacin revealed the formation of phenotypically heterogeneous persisters in them, represented by the SCV (small colony variant) and NCV (normal colony variant) forms. There was no correlation of persister formation between these antimicrobial drugs (R=-0.37), which indicates different mechanisms of tolerance to antibiotics. The ability of amikacin to induce the formation of SCV persisters was higher than that of meropenem (p-level > 0.05), and the synergistic effect of both drugs contributed to a decrease in their number, to a maximum of 80.0%. At the same time, SCV-persists of K.pneumoniae were characterized by a short-term increase in adaptive resistance to antibiotics, which were used as inducers of the formation of persistent bacterium fractions (p-level > 0.05), which may contribute to their more effective survival in media with antibiotics.